Global Trends in Rural People Livelihood Practice of Raft Culture of Red Seaweed, Kappaphycus alvarezii in Gujarat, India - Bhatt A, Nakul; Sharma, B. K.; Vaghela, D. T.; D, Divu (International Journal of Bio-resource and Stress Management, 2018)
India is rich in biodiversity, especially of marine biodiversity. Marine biodiversity includes both flora and fauna. There are 20,000 species of seaweed worldwide, half of them are economically important and 280 are edible. Kappaphycus is a red alga belonging to Rhodophyceae. It grows profusely in the sea where the bottom is sandy and salinity ranges from 29-34 ppt. it requires only sunlight, transparent seawater with mild wave action for replenishing bottom nutrients. It has also been proved that Kappaphycus grow >10 times in open sea where wave action is fairly high. Kappaphycus is carrageen yielding res algae cultivated amount of south pacific countries. In Gujarat, Kappaphycus grows to throw vegetative propagation using floating rafts. An experimental on Kappaphycus cultivation at five different cultivation sites wiz, Okha, Dwarka, Porbandar, Chorwad and Veraval. The growth was major at an interval of 15 days. The final weights were major at 45th to 60th days. It was observed that maximum vegetative growths were exhibited by Okha center wild lowest growth was observed in Porbandar. The DGR (%) was found to be maximum at Okha site 61.35 kg, 54.75 kg and 33.15 kg wild to lowest DGR (%) was observed at Porbandar 33.15 kg, 22.2 kg and 20.2 kg. Further, it was significantly correlated to salinity at Dwarka, Okha while at Porbandar and Chorwad, Veraval the same was significantly correlated to nitrate and seawater temperature. Based on this study, commercial cultivation at these localities is quite feasible.